COMPARATIVE ANALYSIS OF MANAGEMENT OF HIGHER EDUCATION SYSTEMS IN GREECE AND GERMANY (EDUCATION IN THE 21ST CENTURY, 2023)
This article, based on the example of two countries - Greece and Germany, shows a differentapproach to their higher education systems for the preparation of qualified specialists in scienceand culture.Greece, as a country with an ancient and rich historical heritage, attracts many applicants forhigher education with high academic records.External governing bodies of higher education in Greece include: central government - theMinistry of Education and Religious Affairs of Greece, district government - regional educationauthorities, local government - higher education institution. Internal governing bodies include: theUniversity’s Senate, the Rector's Council, the Rector, the General Assembly, the Student’s Union,Deans of faculties, Heads of departmentsIn Germany, the external governing bodies of higher education are: the central government -the Ministry of Education and Culture, the Permanent Conference of the Ministers of Educationand Culture of the Lands, regional. bodies - the Regional Special Ministries, the local government- the university, the Conference or the Council of Rectors of German universities. Internalgoverning bodies are: the rector or president of the university, the Academic Council, the StudentCouncil, deans of faculties, heads of departments.In Greece, higher education is financed by the state budget, non-state funds, as well asthrough private payments. In Germany, funding for higher education is provided by the statebudget, the states, the Germany Union of Research Assistance and private individuals.For admission to Greek universities, an applicant must provide a certificate of completion ofsecondary education, and for German universities - ABITUR diploma or competitive selectionbased on the results of entry exams. For admission to universities in Greece, knowledge of theGreek language is mandatory both for Greeks and for foreigners. The Germany language ismandatory for Germany universities also both for Germans and foreigners.Greek universities have a 10-point grading system, and German universities have a 6-pointgrading system.In Greek universities, training takes place in three stages: bachelor's degree - 4-5 years,master's - 1-3 years, doctoral studies - 3 years. In German universities - basic - 3-4 semesters, main- 4-6 semesters, doctoral studies - 3-4 years.Thus, European higher education is one of the most highly rated forms of education, therating of which is increasing every year.
Keywords: higher education system, education system bodies, financing, grading, admission, structure of higher education.